Biomedical Engineering for Medical Assistance "Stress and Acceleration Analysis for Damage Half-skull as A Consequence of Concrete Impact on a Protective Helmet" (Mechanical and Computer Engineering). Issue 1 (January 2021) - Sakly, Houneida; Said, Mourad; Tagina, Moncef
Abstract: The dynamic analysis of fluid mechanics CFD applied to the medical field is one of the most important structural problems. They impose additional mechanical constraints on the construction of the 3D model to be processed and reduce its performance. As the acceleration forces of the concrete mainly excite these contacts between the skull and the Helmet, they could taken into consideration in this proposed system (helmet, concrete, and skull). Our aim is to evaluate the stress measurements in an accidental half-skull 3D with the computer fluids dynamics (CFD) tools basing on the mechanical and physical properties of the wall the skull. The second contribution is to analyze the acceleration of a concrete and the impact in the stress evaluation on half skull with and without helmet.